Effect of Branch Bending on Fruit Production and Quality of Different Varieties of Guava (Psidium guajava L.) - Kumar, Rajnish; Tiwari, Divya; Kumari, Dhyanananda; Sinha, Neha; Kumar, Ajeet; Azad, C. S.; Behera, Subrat Kishori; Kumar, Randhir (International Journal of Bio-resource and Stress Management, 2025)
The present investigation was carried out from January to August, 2024 in a guava orchard at Nalanda College of Horticulture, Noorsarai (Nalanda), Bihar, to evaluate the effects of branch bending and pruning on vegetative growth, flowering, fruit yield, and quality of different guava varieties. The experiment followed a Factorial Randomized Block Design with twelve treatment combinations and three replications, involving three guava varieties-Lucknow-49 (V1), Lalit (V2), and Allahabad Safeda (V3)-subjected to four pruning and bending treatments: B0 (control), B1 (bending of lateral branches and partial removal of older leaves), B2 (One leaf pair pinching with complete removal of old leaves), and B3 (Removal of leaves, keeping 10 to 12 pairs of leaves intact at the terminal portion of each branch). Results revealed that B1 treatment significantly enhanced early shoot emergence (12.49 days), vegetative growth, and reproductive parameters, with V2 (Lalit) showing the shortest shoots. Flower initiation and fruit set occurred earliest in B1 (42.39 and 60.59 days, respectively), while V1 (Lucknow-49) exhibited early fruit maturity. B1 treatment yielded the highest fruit set (68.67%) and retention (74.67%), with the V3B1 combination producing the heaviest fruits (117.72 g) and highest pulp-seed ratio (41.18). B1 also led to the highest fruit count (117.78 fruits plant-1), yield (12.54 kg plant-¹), and productivity (90.90 q ha-¹ with V1B1). Biochemical analysis confirmed superior fruit quality under B1, with maximum total soluble solids (10.64°Brix), total sugars (6.57%), and ascorbic acid (178.31 mg 100 g-¹ pulp), and also superior quality with Lalit (V2) highlighting its overall efficacy.